Respostas

2014-05-11T17:31:17-03:00
X²+x-12=0
Δ=(1)²-4.1.(-12)
Δ=1+48
Δ=49

x=-1±√49
       2

 x=-1 ±7
         2
 x'=-1-7= -8/2 = -4
       2  
x''= -1+7= 6/2 = 3 

s={-4,3}   
2 5 2
o qu estiver sobre 2, é uma fração q eu no consegui reproduzir xD
VLLW <33
2014-05-11T17:34:56-03:00
X² + x - 12 = 0
a = 1 ; b = 1 ; c = -12

Δ = b² - 4.a.c
Δ = 1² - 4.1.(-12)
Δ = 1 + 48
Δ = 49

x = (-b + - √Δ) / 2.a
x = (-1 + - √49) / 2.1
+x = (-1 + 7) / 2
+x + 6 / 2 = 3

-x = (-1 - 7) / 2
-x = - 8 / 2 = - 4

S = ( 3 ; - 4 )
1 5 1